GAMBARAN HARGA SAHAM DITINJAU DARI TINGKAT INFLASI, NILAI TUKAR RUPIAH, DAN SUKU BUNGA: STUDI KASUS PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45 - Andi Amri; Ramadhi; Mitra Sami Gultom (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
The background of this research, the existence of stock price fluctuations which makes investors must be observant in analyzing stock prices. Otherwise, investors will suffer huge losses. In addition, increases in inflation, the rupiah exchange rate, and book rates are among the factors that affect stock prices, so that stocks become out of control and continue to increase. The objectives of this study are 4, namely to analyze the inflation rate on stock prices, the rupiah exchange rate for stock prices, interest rates on stock prices, and finally to analyze together the influence of inflation rates, rupiah exchange rates, and interest rates on stock prices. especially for companies listed on the LQ45 Index. This type of descriptive quantitative research with purposive sampling method of sampling at the LQ45 company which consists of 45 companies, in order to obtain 225 observations for each variable. The data source for the company's annual report uses the data analysis technique, namely panel data regression. The results of the research that have been done can be concluded that partially inflation, exchange rates, and interest rates have a significant and significant effect on stock prices. Meanwhile, simultaneously both have an influence on stock prices and have an adjust R Square value of 88.93% and 11.07% influenced by other factors not present in this study.